AKTIVITAS PENGHAMBATAN EKSTRAK BERBAGAI JENIS BAWANG TERHADAP PEMBENTUKAN BLACKSPOT PADA UDANG VANAME - Tatty Yuniati; Sukarno Sukarno; Nancy Dewi Yuliana; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Blackening is a problem occurring in crustaceans, such as whiteleg shrimps (Litopenaeus vannamei), during post-mortem storage. Although blackspot seems to be harmless to consumers, it decreases the product’s market value, consumer’s acceptance and causes a considerable financial loss. The objective of the study was to determine the best Allium extracts from five Allium types with the ability to inhibit blackspot and apply the extracts on whiteleg shrimp. The five types of Allium were red onion (Allium cepa L. var Aggregatum), garlic (Allium sativum), yellow onion (Allium cepa Linneaus), leek (Allium fistulosum) and chives (Allium schoenoprasum L). Extraction of Allium was conducted using 80% methanol as the solvent. The dry extracts were tested in vitro using a commercial polyphenol oxidase (PPO) enzyme and a melanosis test was conducted on whiteleg shrimp treated with the extracts and stored at 0°C for 10 days. The results showed that the highest inhibition of blackspot formation was obtained by red onion extract at 69.79±1.91% and the lowest was by garlic extract at 14.06±1.41%. The shrimps dipped in red onion extract had the lowest melanosis values and browning index values at 5.1±0.8 and 16.76±0.94, respectively. Red onion extract had the best ability to inhibit blackspot and has the potential to be used in shrimp.